2014
DOI: 10.1063/1.4897258
|View full text |Cite
|
Sign up to set email alerts
|

Calculating time-resolved differential absorbance spectra for ultrafast pump-probe experiments with surface hopping trajectories

Abstract: We report a surface hopping approach for modeling the full time- and frequency-resolved differential absorbance spectra (beyond the inhomogenous limit) obtained in ultrafast pump-probe experiments. In our approach, we combine dynamical information obtained from ensembles of classical trajectories propagated on the ground and on the excited potential energy surfaces to directly calculate optical response functions and hence spectral lineshapes. We demonstrate that our method is exact for the model problem of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 82 publications
(116 reference statements)
1
47
0
Order By: Relevance
“…31,59 Note that this approach effectively combines the dynamical information present in eqs 7 and 8. We previously demonstrated that eq 10 is exact for the case of uncoupled shifted harmonic potentials with identical harmonic frequencies and agrees with the formalism of Kapral and Martens in the short-time limit.…”
Section: Linear Absorption Spectra In the Absencementioning
confidence: 98%
See 2 more Smart Citations
“…31,59 Note that this approach effectively combines the dynamical information present in eqs 7 and 8. We previously demonstrated that eq 10 is exact for the case of uncoupled shifted harmonic potentials with identical harmonic frequencies and agrees with the formalism of Kapral and Martens in the short-time limit.…”
Section: Linear Absorption Spectra In the Absencementioning
confidence: 98%
“…31,59 Note that this definition combines information from both the electronic wave functions carried by the FSSH trajectories and the active adiabatic surfaces that they are propagated on at time t. Similarly, the electronic coherence between diabats a and b can be obtained by combining eq 16 with U(x⃗ ) …”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…Field-induced couplings were the subject of more studies where the absorption spectra [35][36][37]54 or laser-induced transitions 33,[38][39][40][41] were calculated with the surfacehopping methodology. Spin-orbit and dipole couplings have been recently treated simultaneously with surfacehopping method 31,33,43,44 .…”
Section: Introductionmentioning
confidence: 99%
“…The surface-hopping methodology allows the study of radiative association with electronic transitions to be extended to arbitrary polyatomic system. The surface-hopping method is widely used in the modeling of nonadiabatic molecular processes [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] . The idea of this method originally put forward by Bjerre and Nikitin 48 and later advanced by others [49][50][51][52][53] .…”
Section: Introductionmentioning
confidence: 99%